The Dawn of Malaysia, development Experience and an economic success - Larbi, Larbi (IJRDO - Journal of Social Science and Humanities Research, 2019)
In a short period, Malaysia has been able to record improvement across all sectors. This is due to the well-established policies and strategies that have been able to fight poverty and raise incomes, as well as the elimination of the conflicts that existed between the different ethnic races of the Malaysian state. This behavior raised allegiance from the tribe to a wider space, the Malaysian nation. Its economy was developed, and take a good place in the international community through excellence in the field of technological creativity, which baffled developed Western countries. A remarkable experience deserves study and reflection.